People: Summer School of Architecture, Monastery of St. Joachim Osogovski - Bakalchev, M., Hadzi-Pulja, M., Tasić, S. (Архитектонски факултет-Скопје, 2016)
Learning / education is connected with idea, program, methods of learning. But what about the people? What about all those participants in learning, their features, characteristics, values, weaknesses? Debates on learning centered on ideas / ideology, strategies, policies of educating and of course they are presented/represented/defended by different individuals, but the individuals remain as background in the process of learning - self-evident fact, the background of abstract ideas and models of learning. But is it so? Whether individuals can be excluded from the process of educating or perhaps they constitute it? In the various debates basic ideas embodied in the personsare excluded. The models operate on the basis of abstraction and participants only realized the various procedures of learning and their particular personality are suppressed and relativized.
Keywords: individuals, mentors, teachers, ideologies, criticism, the process of learning